2018
DOI: 10.1158/2326-6066.cir-17-0320
|View full text |Cite
|
Sign up to set email alerts
|

YAP-Induced PD-L1 Expression Drives Immune Evasion in BRAFi-Resistant Melanoma

Abstract: Activation of YAP, a Hippo pathway effector, is an important resistance mechanism to BRAF inhibitor (BRAFi) in melanoma. Emerging evidence also suggests that YAP is involved in suppression of the antitumor immune response. However, the potential direct impact of YAP activity on cytotoxic T-cell immune responses has not been explored yet. Here, we show that BRAFi-resistant melanoma cells evade CD8 T-cell immune responses in a PD-L1-dependent manner by activating YAP, which synchronously supports melanoma cell s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
145
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(161 citation statements)
references
References 50 publications
10
145
0
Order By: Relevance
“…YAP/TAZ levels were decreased using siRNA and PD‐L1 expression was assessed after TGFβ treatment. As shown in FigureB, YAP/TAZ knockdown prevented TGFβ stimulated PD‐L1 expression in both human and murine fibroblasts, consistent with previous reports that PD‐L1 is a direct transcriptional target of YAP/TAZ in several tumor models …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…YAP/TAZ levels were decreased using siRNA and PD‐L1 expression was assessed after TGFβ treatment. As shown in FigureB, YAP/TAZ knockdown prevented TGFβ stimulated PD‐L1 expression in both human and murine fibroblasts, consistent with previous reports that PD‐L1 is a direct transcriptional target of YAP/TAZ in several tumor models …”
Section: Resultssupporting
confidence: 91%
“…As shown in Figure5B, YAP/ TAZ knockdown prevented TGFβ stimulated PD-L1 expression in both human and murine fibroblasts, consistent with previous reports that PD-L1 is a direct transcriptional target of YAP/TAZ in several tumor models. [47][48][49]…”
Section: Yap/taz Regulates Pd-l1 Expression By Tgfβmentioning
confidence: 99%
“…Indeed, the expression of miR-130a mimic or miR-130a sponge suppressed or enhanced VGLL4 and PD-L1 levels, respectively, in A549 cells (Fig 6A-C). Consistent with previous reports Lee et al, 2017;Miao et al, 2017;Janse van Rensburg et al, 2018;Kim et al, 2018), we observed an increased PD-L1 mRNA level when YAP5SA, a transcriptionally active and Hippo pathway-resistant YAP mutant, was expressed in A549 cells (Fig EV5B). Consistent with previous reports Lee et al, 2017;Miao et al, 2017;Janse van Rensburg et al, 2018;Kim et al, 2018), we observed an increased PD-L1 mRNA level when YAP5SA, a transcriptionally active and Hippo pathway-resistant YAP mutant, was expressed in A549 cells (Fig EV5B).…”
Section: Yap Inhibits Ifnc-inducible Pd-l1 Expressionsupporting
confidence: 92%
“…Recently, several studies suggest that YAP/TAZ promote PD-L1 expression through TEAD-mediated transcriptional regulation Lee et al, 2017;Miao et al, 2017;Janse van Rensburg et al, 2018;Kim et al, 2018). Interestingly, one study showed that VGLL4 expression is repressed by YAP/TEAD transcriptional complex through miR-130a , which promotes us to test whether miR-130a and YAP could suppress IFNc-inducible PD-L1 expression.…”
Section: Yap Inhibits Ifnc-inducible Pd-l1 Expressionmentioning
confidence: 99%
See 1 more Smart Citation